2019
DOI: 10.1111/ijfs.14382
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, rheological and sensory characteristics of sweet spreads made from by‐products of soya bean and maize

Abstract: Summary Sweet maize cob (SMC) and black soya bean seed coat (BSC) were used to prepare a sweet spread. Chemical composition of the prepared spread and its rheological and sensory characteristics were investigated. The results were compared with those of commercial plum and raspberry jams and spreads. Spreads made from SMC and BSC had the highest content of proteins, total fibres, hemicellulose and cellulose. In relation to fruit jams, they are distinguished by the presence and content of p‐coumaric, ferulic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Soybean kernels were manually dehulled, and seed coat was ground in a laboratory mill (Perten 120 lab mill, Perten, Hägersten, Sweden) to fine powder (particle size < 500 µm) and stored at −70 • C prior to the extraction of anthocyanins. Based on our previous study [17], black soybean seed coat contained 40,762.2 mg GAE/kg of total phenolic compounds and 11,883.90 mg GGE/kg of total anthocyanins, with cyanidin 3-glucoside as the dominant (3387.10 µg/g). The antioxidant capacity of black soybean seed coat determined by QUENCHER method was 399.5 mmol Trolox Eq/kg.…”
Section: Plant Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…Soybean kernels were manually dehulled, and seed coat was ground in a laboratory mill (Perten 120 lab mill, Perten, Hägersten, Sweden) to fine powder (particle size < 500 µm) and stored at −70 • C prior to the extraction of anthocyanins. Based on our previous study [17], black soybean seed coat contained 40,762.2 mg GAE/kg of total phenolic compounds and 11,883.90 mg GGE/kg of total anthocyanins, with cyanidin 3-glucoside as the dominant (3387.10 µg/g). The antioxidant capacity of black soybean seed coat determined by QUENCHER method was 399.5 mmol Trolox Eq/kg.…”
Section: Plant Materialsmentioning
confidence: 98%
“…More than 99% of the total anthocyanins in black soybean seed coats (BSSCs), which largely contribute to the colour, are assumed to be located in the epidermal palisade layer [15]. Many studies have shown that BSSCs rich in polyphenols and dietary fibres can be used as bioactive ingredients in functional foods and pharmaceutical products for targeting different health problems [17]. In addition, black soybean extracts rich in bioactive compounds have so far been utilized in the preparation of noodles [18][19][20], crackers [21], touhua (soft soybean curd) [22] and biodegradable films [23,24].…”
Section: Introductionmentioning
confidence: 99%